Numerical Analysis of Compound Walls of Brick Masonry, Strengthened with C-FRP Laminate under Explosive Detonations - Afghanistan Scenario - Anas S.M.; Al-Dala'Ien R.N.; Alam M.; Kanaan M.H.G.; Akram S.; Haris M. (EDP Sciences, 2024)
Afghanistan, a nation plagued by wars, terrorism, and counter-terrorism, has borne the brunt of these conflicts. The common people of Afghanistan are weary of the continuous cycle of attacks and counterattacks by warlords. Even places of worship and those who gather there are not spared from these acts of violence. For years, explosive blasts have targeted the compound walls surrounding these religious structures. In this research, we investigate the impact of such blasts on free-standing URM walls commonly used in Afghanistan. Using ABAQUS/Explicit code, we conduct nonlinear analysis to examine the blast performance of these walls. Additionally, we retrofit the walls with a high-strength C-FRP laminate. To optimize computational time, we employ a macro strategy. The results show that the strengthened walls exhibit comparable blast performance. Importantly, when the laminate is applied to both faces, there is no longer a need for increased wall thickness in the masonry construction. The Authors, published by EDP Sciences. This is an open access article distributed under the terms of the Creative Commons Attribution License 4.0 (https://creativecommons.org/licenses/by/4.0/).